A Comparative Study of Iran’s Electricity Market Auction Mechanism and System Marginal Price Auction Mechanism - Jamshid Pajuyan (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2014)
The present article discusses the impacts of selecting between different common auctions in electricity markets (system marginal price auction and pay as bid auction) on production efficiency, total efficiency and average expected price in an asymmetric information situation, where each player’s information about the marginal cost of the competitor is incomplete. A simple model is designed to conduct the comparative study of alternative auction mechanisms. The model is based on two profit maximizing players, with full information about their own marginal cost and incomplete information about their competitor. Assumptions which have been used to construct the model are based on Iran’s electricity market structure. The outcome indicates that although players bid functions in alternative auction mechanism differ from each other, the production efficiency, total efficiency and the average expected price are equivalent.